The protective effects of humanin in rats with experimental myocardial infarction: The role of asprosin and spexin - Onat, Elif; Kocaman, Nevin; Hancer, Serhat (Cell Press, 2023)
Objective: In this study, by applying humanin (HN) before myocardial infarction (MI) in rats, its protection in MI and the possible roles in asprosin and spexin were investigated.Materials and methods: The rats were divided into 7 groups each with 6 rats (group I (control), group II (HN 48th hour), group III (HN 7th day), group IV (MI 48th hour), group V (MI 7th day), group VI (MI + HN 48th hour), group VII (MI + HN 7th day). To create MI, 200 mg/kg isoproterenol (ISO) was administered subcutaneously to the rats. 2 mg/kg HN was given intraperitoneally (ip) to rats alone and before MI. Molecular parameters asprosin and spexin were examined by immunohistochemical in heart tissue. Biochemical parameters (aspartate aminotransferase (AST), lactate dehydrogenase (LDH), creatine kinase MB (CK-MB), Troponin I) were studied in serum by enzyme-linked immunosorbent assay (ELISA) method.Results: It was found in the study that the levels of spexin elevated especially towards the 7th day after MI and decreased more significantly towards the 7th day, after HN application before MI. Asprosin elevated significantly towards the 7th day after MI and decreased especially on the 7th day after HN application before MI. Also, serum AST, LDH, CK-MB, and Troponin I levels tended to decrease and a significant decrease was detected in congested veins in the heart tissue at the 48th hour of MI and erythrocyte extravasation, congested veins and necrotic muscle fibers at the 7th day of MI in rats given HN before MI.Conclusion: It was concluded that HN has a cardioprotective effect in MI and asprosin and spexin might mediate this effect.
Keywords: Myocardial infarction; Humanin; Asprosin; Spexin